Update on perioperative hypersensitivity reactions: joint document of the Brazilian Society of Anesthesiology (SBA) and Brazilian Association of Allergy and Immunology (ASBAI) – Part I: post-crisis guidelines and treatment - Spindola,Maria Anita Costa (2020)
Abstract Experts from the Brazilian Association of Allergy and Immunology (ASBAI) and the Brazilian Society of Anesthesiology (SBA) interested in the issue of perioperative anaphylaxis, and aiming to strengthen the collaboration between the two societies, combined efforts to study the topic and to prepare a joint document to guide specialists in both areas. The purpose of the present series of two articles was to report the most recent evidence based on the collaborative assessment between both societies. This first article will consider the updated definitions, treatment and guidelines after a perioperative crisis. The following article will discuss the major etiologic agents, how to proceed with the investigation, and the appropriate tests.